2011
DOI: 10.1177/0192623311428476
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Increased Sensitivity of Pregnant and Lactating Female Rats to Immunotoxic Agents

Abstract: Characteristic susceptibility to environmental and pharmaceutical exposure may occur during periods in life of marked histophysiological changes of the immune system. Perinatal development is such a period; pregnancy followed by lactation is potentially another one. Here, we explored the influence of pregnancy and lactation on the model immunotoxic compound di-n-octyltin dichloride (DOTC) in rats using clinical and histopathological parameters. Female rats were exposed to 0, 3, 10, or 30 mg DOTC/kg feed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…25 Reduction in lymphoid cellularity and alterations in the corticomedullary ratio, had been regarded as deleterious effect of xenobiotics on the thymus, and is considered as a highly sensitive indicator of immunotoxicant exposure. 26 The reduction in the lymphoid cellularity in spleen of CY treated rats is in agreement with previous studies that observed depletion of T lymphocytes in mice treated with a single dose of 4 mg, 27 and 200 mg/kg of CY, 28 and decreased cellularity in the spleen in rats treated daily with 10mg/kg CY for 30 days. 19 Several studies have reported that naturally extracted remedies that possess high antioxidant property showed protective effects on CY-induced myelosuppression and cytotoxicity in lymphoid tissues.…”
Section: Discussionsupporting
confidence: 92%
“…25 Reduction in lymphoid cellularity and alterations in the corticomedullary ratio, had been regarded as deleterious effect of xenobiotics on the thymus, and is considered as a highly sensitive indicator of immunotoxicant exposure. 26 The reduction in the lymphoid cellularity in spleen of CY treated rats is in agreement with previous studies that observed depletion of T lymphocytes in mice treated with a single dose of 4 mg, 27 and 200 mg/kg of CY, 28 and decreased cellularity in the spleen in rats treated daily with 10mg/kg CY for 30 days. 19 Several studies have reported that naturally extracted remedies that possess high antioxidant property showed protective effects on CY-induced myelosuppression and cytotoxicity in lymphoid tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Relative thymus weight of untreated pregnant and lactating female rats was 46% of age‐matched dioctyltin dichloride (DOTC)‐treated nonpregnant and nonlactating females. By postnatal Day 56, thymus weight and immune function had recovered (Menke et al, 2012). Certain butyltin substances were also shown to cause developmental effects.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, organotin (IV) compounds when applied as anti-cancer metallodrugs, have efficacy comparable to the platinum-based cisplatin (Attanzio et al, 2020). DMTC is associated with neurotoxicity, trimethyltin chloride and dioctyltin dichloride (DOTC) are associated with thymic toxicity which is dose dependent and reversible (Menke et al, 2012). Under the Globally Harmonized System of Classification and Labelling of Chemicals (GHS) and the legal framework for classification and labelling in the EU (CLP Regulation) DMTC is classified as Reprotoxicant of Category 2 (H361d) as it induced developmental toxicity in experimental fertilized animals (ECHA, 2012).…”
Section: Introductionmentioning
confidence: 99%